2002
DOI: 10.1103/physrevlett.89.213401
|View full text |Cite
|
Sign up to set email alerts
|

Background-Free Observation of Cold Antihydrogen with Field-Ionization Analysis of Its States

Abstract: A background-free observation of cold antihydrogen atoms is made using field ionization followed by antiproton storage, a detection method that provides the first experimental information about antihydrogen atomic states. More antihydrogen atoms can be field ionized in an hour than all the antimatter atoms that have been previously reported, and the production rate per incident high energy antiproton is higher than ever observed. The high rate and the high Rydberg states suggest that the antihydrogen is formed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
197
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 527 publications
(203 citation statements)
references
References 18 publications
2
197
0
1
Order By: Relevance
“…Low-energy antihydrogen was first synthesized 2 in 2002. This feat was later repeated [7][8][9] , and in 2010 antihydrogen was successfully trapped 3 to facilitate its study. It was subsequently shown that antiatoms could be held 4 for up to 1,000 s, and various measurements have been performed on antihydrogen in the context of tests of CPT symmetry [10][11][12] or gravitational studies 13 .…”
mentioning
confidence: 99%
“…Low-energy antihydrogen was first synthesized 2 in 2002. This feat was later repeated [7][8][9] , and in 2010 antihydrogen was successfully trapped 3 to facilitate its study. It was subsequently shown that antiatoms could be held 4 for up to 1,000 s, and various measurements have been performed on antihydrogen in the context of tests of CPT symmetry [10][11][12] or gravitational studies 13 .…”
mentioning
confidence: 99%
“…Two attempts, at Stanford [13] and CERN's Low-Energy Antiproton Ring [14] were thwarted by the overwhelming effect of stray electric and magnetic fields upon the electrically charged test particles. The recent production of copious amounts of cold antihydrogen ðHÞ at CERN's Antiproton Decelerator (AD) [15,16] has paved the way for high-precision gravity experiments with neutral antimatter. We have proposed the AEGIS experiment (Antimatter Experiment: Gravity, Interferometry, Spectroscopy), to be performed at CERN/AD, in order to address this important question.…”
Section: Introductionmentioning
confidence: 99%
“…The standard model is the theory that describes particles and their fundamental interactions, although without taking into account gravitation. However, this model is known to be incomplete, which has inspired searches for physics beyond the standard model, such as tests of CPT invariance that compare the fundamental properties of matterto-antimatter equivalents at the lowest energies and with the greatest precision [12][13][14][15] . For leptons, for example, the magnetic anomalies of electron and positron were compared with a fractional uncertainty of about 2 parts per billion 4 , and by applying similar techniques to protons and antiprotons, the resulting g-factor (a proportionality constant which links the spin of a particle to its magnetic moment) comparison reached a precision of 4.4 parts per million 8 .…”
mentioning
confidence: 99%